A Randomised Comparative Clinical Study to Evaluate the Efficacy of Sadhyovirechana followed with Chakramarda Lepa and Aragvadadi Lepa in the Management of Dadru (AYUSHDHARA, 2025)
Dadru is classified as Ksudra Kushta by Acharya Charaka and as Maha Kushta by Acharya Sushruta and Vagbhata. It results from vitiation of Kapha and Pitta as Pradhana Dosha and is treated with Shodhana and Bahya Lepa Chikitsa. Modern management of Tinea involves antifungals and corticosteroids, but prolonged use causes side effects. Ayurveda offers a better treatment. This study evaluates Sadhyovirechana as Abhyantara Shodhana Chikitsa followed by Bahya Chikitsa in the form of Lepa Karma, applied to two groups to assess their efficacy in managing Dadru Kushta. Aims and Objectives of the Study: 1. To evaluate the Efficacy of Sadhyovirechana followed with Chakramarda Beeja Choorna Lepa in the Management of Dadru Kushta. 2. To evaluate the Efficacy of Sadhyovirechana followed with Aragvadadi Lepa in the Management of Dadru Kushta. 3. To compare the efficacy of both the groups in Dadru Kushta. Materials and Methodology: This is a comparative clinical study with pre-test & post-test design. A total of 40 patients diagnosed with Dadru Kushta were selected, irrespective of sex, religion, occupation, or economic status. They were randomly divided into two groups of 20 patients each: Group A and Group B. Intervention: Group A: Sadhyovirechana followed by Chakramarda Lepa for next 7 Days. Group B: Sadhyovirechana followed by Aragvadadi Lepa for next 7 Days. Observations and Results: The treatment outcomes in both groups were assessed by applying Wilcoxon’s rank sum test within the groups and Mann-Whitney U test between the groups. Patients in Group A demonstrated significantly better results compared to Group B. Discussions and Conclusion: The study concludes that Sadhyovirechana followed by Chakramarda Lepa and Aragvadadi Lepa Chikitsa plays a significant role in effectively managing and curing Dadru Kushta.